Evaluation of the E-Peken Surabaya Website Quality Using Modified Webqual 4.0 and Importance Performance Analysis - Galih Aulia Murdyahanjani; Asif Faroqi; Tri Lathif Mardi Suryanto (Komunitas Dosen Indonesia, 2025)
E-Peken Surabaya is a web–mobile platform initiated by the Surabaya City Government to empower local economic actors, including MSMEs, food stalls (SWK), and local stores. Since its implementation in 2023, users have reported usability issues, highlighting the need for an evaluative study on service quality. This research adopts a descriptive-quantitative method using purposive sampling, with a total of 385 respondents selected based on active usage. Data collection employed a modified WebQual 4.0 questionnaire integrated with additional variables such as Reliability, Trust, Citizen Support, and Efficiency to capture comprehensive user perceptions. Data were analyzed using SPSS, with Pearson’s r for validity and Cronbach’s Alpha for reliability testing. Using Importance Performance Analysis (IPA), eight indicators were identified in Quadrant I (High Importance Low Performance), which require immediate strategic intervention. These include interface responsiveness (UI/UX), completeness and clarity of product information, accessibility of communication channels, consistency in system maintenance, and assurances in data privacy and security. These areas demonstrated significant negative gaps between perceived importance and performance, suggesting that user satisfaction is being compromised in core service aspects. The integration of WebQual 4.0 and IPA proves effective in isolating service components most in need of reform. As a strategic response, the study recommends incremental improvement planning, periodic performance audits, and scalable solutions to optimize user experience and enhance platform reliability.